Effect of reaction time on zinc oxide nanoparticle synthesized with banana peel extract - Ali Sabri, Hazirah (2018)
Zinc oxide can be synthesis by using various methods. Zinc oxide have multifunctional methods therefore it use in wide range of applications. The first objective of this study is to synthesize zinc oxide nanoparticle through a green synthetic pathway using banana peel extract. In order to identify the functional group exists in the banana peel, the FTIR is used. In this study, the third objective is to study the effect of time variation on the properties of the synthesis of zinc oxide nanoparticles from banana peel. The last objective is to characterization of zinc oxide nanoparticles after it has been synthesized by using Ultraviolet- Visible spectrophotometer (UV-Vis), X-ray Powder Diffraction (XRD), Fourier Transform infrared spectroscopy (FTIR), and Brunauer, Emmett and Teller (BET). The method use, in this research is green synthesis of zinc oxide nanoparticles using plant extract.